LEXICAL PROBLEMS OF TRANSLATION (Ustozlar uchun, 2026)
The issue of translating from one language into another is still relevant. Translation of lexical units plays a significant role in the theory of translation. The article highlights the right techniques of translation of words, analyses the specifics of translation of lexical units. Theoretical aspects are illustrated by examples of words and word combinations.